Corona Virus – The Dental Outlook - Pravallika, Dr. Thorikonda Sai; Akula, Dr. Sheetal; Balaji, Dr. Kurnool; Jyothi, Dr. Maddela; Reddy, Dr. Jaidupally Ramvilas (International Journal of Scientific Research and Management (IJSRM), 2020)
AIM: This review provides an overview of the corona virus and to determine the precautionary recommendations to be taken by the Dental Professionals.BACKGROUND: Corona virus (COVID-19) in no time has captured the world’s attention and is declared as a pandemic by WHO.REVIEW RESULTS: Dental care settings inevitably carry the risk of infection due to the specificity of the procedures and effective preventive measures can help the spread of the infection.CONCLUSION: The outbreak of corona virus had already lead to huge number of deaths and its risk continues to remain high. Infection control measures are necessary to help control the situation.KEYWORDS: Corona virus, Pandemic, Dental considerations